MANAGEMENT OF THE TECHNICAL RESOURCE OF MILITARY EQUIPMENT OF THE VIETNAMESE PEOPLE’S ARMY - M. K. Nguen; I. Ivanov (Вестник университета, 2017)
The problem of controlling the maintenance of military equipment of the Vietnamese People's Army is presented. The tasks on managing the technical resource have been formulated and the most effective solutions have been identified.